P473 Real world experience with the Crohn's Disease Exclusion Diet (CDED) in a tertiary IBD clinic. (21st January 2022) - Fliss Isakov, N; Anbar, R; Cooperstein, A; Helbert, G; Hirsch, A; Ron, Y; Thurm, T; Maharshak, N
Abstract: Background: The Crohn's Disease Exclusion Diet (CDED) is a whole-food diet designed to reduce exposure to dietary components, hypothesized to negatively affect the microbiome, intestinal barrier, and immune response. In a clinical study in adults with mild-moderate CD (<5 years duration), an inflammatory phenotype involving the terminal ileum, it induced clinical, biochemical and endoscopic disease remission. We aimed to describe our real-world experience with the CDED, in a clinically diverse CD population. Methods: A retrospective cohort study of CD patients prescribed with the CDED, between 1.2018 and 11.21. Patients' medical background, medical therapy, nutritional status and clinical disease activity as well as adherence and clinical outcomes were documented from patients' medical files. Results: The CDED was recommended to 218 CD patients. Of these, 62 were excluded from the analysis due to lack of medical information (n=11), prior personal experience with the CDED (n=23), patient's refusal (n=24), and stoma patients (n=4). The CDED was initiated in 155 patients (age 37.7±16.3, 66% men, disease duration 7.8±9.6), 35.3% had colonic/ileo-colonic disease, 23.7% and 25% had a stricturing and penetrating disease respectively, 27.5% had a history of intestinal resection, 19.9% had extra-intestinal involvement, and 7.7% had a severe endoscopic disease at diet initiation. Indications for therapy included patient's will (44.7%), adjunctive therapy (23.7%), bridge with biologic induction (20.4%), rescue therapy (3.9%), exhaustion/contraindication of other advanced therapy options (1.4%), de-escalation of biologics (0.7%), preparation for surgery (0.7%), and others (3.9%). Upon initiation, 67.3% (n=105) had an active disease [Harvey Bradshaw index (HBI) ≥5 / Calprotectin ≥250 g/l] and 32.7% were in remission. Physician and dietician follow-up at the end of phase 1 was documented in 89 (57.4%) and 74 (47.7%) of patients with an active disease (mean follow-up period 14.6±9.3 weeks). Fifty-eight percent of patients with dietary follow-up (n=43) were fairly-fully compliant to the CDED. Clinical response (drop in HBI>2 points) and remission (HBI<5) at the end of phase 1, were achieved by 58.9% (n=62) and 57.5% (n=60) of patients who were treated for an active disease (n=105). Clinical remission rate at the end of phase 1 was lower among patients with higher baseline HBI score (P for trend=0.028), lower dietary adherence (P for trend<0.001) and a surgical history (P=0.033). Conclusion: The CDED may have efficacy across different clinical scenarios. Adherence is reasonable, and is associated with higher remission rates among patients treated for an active disease.